Improved identification of the electrocardio-signal for pulsatile ventricular assist devices. (31st October 2017) - Li, Xinghui; Luo, Lin; Zhu, Shidong; Yang, Bibo; Ni, Kai; Zhou, Qian; Wang, Xiaohao
Abstract: We introduce and investigate a method to identify the feature point of an electrocardiogram (ECG) to provide real-time and accurate trigger signals for pulsatile ventricular assist devices (PVADs). An important part of this method is an improved data processing algorithm, in which a differential calculator and another a low-pass filtering were added to avoid drift in the original signal and systematically delay caused by physical devices. The method was systematically illustrated in this article and a test-setup was built based on the LabVIEW program development environment. Both simulations and experiments were carried out to demonstrate the merits of the method. Simulated results based on four typical pathological ECG signals confirm the robustness and adaptability of this method. Experimental results verified the benefits of this method with regard to increased accuracy that can pick up the interested signal accurately in a degree of larger than 99%. This improved technology proposed in this research will be greatly beneficial to simultaneous triggering in VADs and eventually to the heart failure recovery.